The Effect of Instagram Based Learning on Motivation and Japanese Language Skill Development - Amalia, Devi Tiara; Setiana, Soni Mulyawan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
This study aims to analyze the impact of learning through the Instagram platform on the motivation of Japanese language course participants and to analyze the relationship between motivation and the improvement of Japanese language skills. This study uses a quantitative approach with a correlational research design. To analyze intrinsic and extrinsic motivation as well as participants' learning outcome records, a Likert scale questionnaire was used. Japanese language course participants who used the Instagram platform were selected through purposive sampling. Data analysis was conducted using descriptive statistics and Spearman's rank correlation coefficient. The research results show that participants' motivation for intrinsic motivation tends to be more dominant than extrinsic motivation, which indicates that participants' motivation is at a moderate to high level. Analysis using Spearman's rank correlation coefficient shows a significant positive relationship between motivation and improvement in Japanese language skills. Interesting Instagram features such as visual content display and communicative interaction play a very important role in increasing interest in learning as well as learners' motivation during the learning process. These results show that Instagram can be effectively utilized as a language learning medium to enhance motivation and support interactive learning. The results of this study indicate that participant motivation can provide significant learning improvement. The selection of interesting content features also becomes one of the participants' motivations to further enhance their language skills. This study provides empirical insights into the use of social media in language learning and serves as a useful reference for developing more interactive and engaging digital learning strategies.